Monoids and semigroups with applications proceedings of the Berkeley Workshop in Monoids : Berkeley, 31 July-5 August 1989 (World Scientific Publishing Co. Pte Ltd., 1991)
''The purpose of the Berkeley Workshop on Monoids was to give expository talks by the most qualified experts in the emerging main areas of monoid and semigroup theory including applications to theoretical computer science. This was supplemented with current research papers. The topics covered, in an accessible way for the mathematical and theoretical computer community, were: Kernels and expansions in semigroup theory; Implicit operations; Inverse monoids; Varieties of semigroups and universal algebra; Linear semigroups and monoids of Lie type; Monoids acting on tress; Synthesis theorem, regular semigroups, and applications; Type-II conjecture; Application to theoretical computer science and decision problems."--Publisher's website